Correction: A Database of Lapidary Artifacts in the Caribbean for the Ceramic Age. (3rd August 2021) - Queffelec, Alain; Fouéré, Pierrirck; Caverne, Jean-Baptiste
This article details a correction to: Queffelec, A., Fouéré, P. and Caverne, J.-B., 2021. A Database of Lapidary Artifacts in the Caribbean for the Ceramic Age. Journal of Open Archaeology Data, 9, p.2. DOI: http://doi.org/10.5334/joad.74